Quantification of Internal Carotid Artery Stenosis with 3D Ultrasound Angiography - Pelz, J. O.; Weinreich, A.; Fritzsch, D.; Saur, D. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: The aim of this study was to evaluate a new method of three-dimensional ultrasound (3D-US) angiography of carotid vessels including 3D-US quantification of internal carotid artery (ICA) stenosis (ICAS).Materials and Methods: Two neurologists performed native ultrasound scans of the brain-supplying carotid arteries in 73 probands (including 22 patients with 25 cases of ICAS) using a Toshiba Aplio 500 ultrasound machine equipped with the 3 D application of Curefab CS. Additionally, 25 probands underwent contrast-enhanced magnetic resonance angiography (CE-MRA) of the neck vessels.Results: The mean length of the proximal ICA was 32.1 mm ± 9.8 mm & 31.3 mm ± 9.0 mm (each n = 97). The interrater reliability (intraclass correlation, ICC) was 0.75 ± 0.23 for the common carotid artery (CCA, n = 90) and 0.78 ± 0.21 (n = 92) for the ICA. The intermethod agreement between 3D-US angiography and CE-MRA was 0.67 ± 0.19 (n = 45) & 0.66 ± 0.19 (n = 44) for the CCA and 0.79 ± 0.17 (n = 47) & 0.75 ± 0.19 (n = 46) for the ICA. Quantification of ICAS applying 3D-US in comparison to 2D color-coded duplexsonography (2D-CDS) showed a moderate to good intermethod agreement both by the Bland and Altman analysis and by ICC (0.8 & 0.72; with each p < 0.001). The interrater reliability for quantification of ICAS was 0.79; p < 0.001.Conclusion: Native 3D-US angiography of carotid vessels shows good interrater and intermethod agreement in comparison to CE-MRA. Together with a moderate to good intermethod and interrater agreement in the quantification of ICAS, when compared to 2D-CDS, 3D-US angiography is thus a promising complementary imaging technique for carotid artery disease.
Keywords: carotid arteries; angiography; 3 D ultrasound; internal carotid artery stenosis; ultrasound color Doppler